Komodifikasi Dalil Agama di E-Commerce - Andi Nur Ahyani; Muhammad Syahrul Mubarak; Abdul Gaffar; Nasri Akib (Muttaqien Publishing, Lembaga Penelitian dan Pengabdian kepada Mayarakat (P3M) STAI DR. KH.EZ. Muttaqien Purwakarta, 2024)
The use of Qur'anic verses as descriptions in sales has been widely practiced by producers, including in the Shopee application. This verse aims to lead the message visually and contains religious elements, so the correlation between images can attract Muslim consumers. This qualitative research seeks to explore the variety of uses of Qur'anic verses in commercialization in Shopee, describe the forms of reception of Qur'anic verses used in Shopee as a commercialization tool, and explain the factors for using Quranic verses as a commercialization tool. This type of research is a qualitative descriptive analysis with a Sociology of Religion approach and one of Peter L. Berger's theories, Social Construction. The research data comes from observations on shop accounts that use Qur'anic verses, translations, and hadith meanings as descriptions. The results showed five forms of commercialization, including Al-Qur'an verses in memes, Al-Qur'an verses in descriptions, Al-Qur'an verses and Hadith in descriptions, Hadith in descriptions, Hadith in descriptions, and Hadith in pictures and descriptions. The typology of reception in this study is included in the typology of functional reception because the Qurâ€™an was created for humans to respond and direct to specific goals, which eventually gave birth to a motivation to change attitudes and ways of acting in everyday life. This happens because of 3 background factors: the externalization factor is the process of self-adjustment, the objectification factor is the result of self-adjustment, and the internalization factor is when producers and consumers I'd appreciate it if you could understand the meaning in the meme. Â